The Determinants of Motor Vehicle Tax Compliance - Oktarina, Dian; Maulidya, Alifia Andita (Jurnal Akuntansi AKUNESA, 2025)
Motor vehicle taxpayer compliance remains a significant challenge for regional governments in Indonesia, including Mojokerto City. This study examines motor vehicle taxpayer compliance determinants, focusing on taxpayer awareness, tax service quality, and tax sanctions. Data were collected from 109 respondents using a convenience sampling method and analyzed with the Partial Least Squares-Structural Equation Modeling (PLS-SEM) approach via SmartPLS 4.0. The results reveal that taxpayer awareness and tax sanctions significantly and positively influence taxpayer compliance, while tax service quality does not show a significant effect. These findings highlight the crucial role of internal taxpayer awareness and enforcing sanctions for service quality improvements. Practical implications suggest that local governments should prioritize massive tax education campaigns and strengthen the enforcement of tax regulations to enhance taxpayer compliance.